Penerapan Teknik Rajut Crochet Granny Square Pada Longtorso - Adinda Kurnia Putri; Ruhidawati, Cucu (Universitas Negeri Jakarta, 2024)
Crochet knitting is a handicraft product that uses yarn as the main material. Products that can be made are very diverse, one of which is longtorso clothing. The objectives of this research are (1) to create longtorso clothing that can be used as outerwear, (2) to create longtorso clothing that can be used as party clothing, (3) to attract young people to be interested in crochet knitting products. The research methodology used in this research is a three-stage methodology of craft creation which includes; (1) the exploration stage which includes finding the source of ideas, concepts, and the basis of creation, (2) the stage of designing the work design, (3) the stage of realization of the work. After going through these various processes, a longtorso product was produced that can be used on party occasions.